A Profile of Knowledge and Sexual Behaviors Among Textile Workers in Context of HIV And AIDS in Surat City - Modi, Bhautik; Padodara, Jay; Mangukiya, Sarita; Tailor, Vimalkumar (National Journal of Community Medicine, 2010)
HIV infection and AIDS is more prevalent in India and occurs in all states.2 Today, there are around 2.5 million people living with HIV/AIDS in India.1 Surat city in the western state of Gujarat attracts a very large migrant population. As most of them belong to sexually active age group, their exposure to sex workers or having multiple sexual partnerships is very high. The aim of this study was to explore the sexual behavior among textile factory workers in Surat and assess the knowledge and awareness about mode of transmission of HIV. This cross-sectional study of 250 textile workers reveals that 76.4% worker know that HIV can be transmitted by unsafe sexual route while 43.2% of workers does not know that HIV can be spread through reused injections. 43 workers currently had extra marital or premarital sexual relations and among them 48.8% had used condom during last such intercourse.